2019
DOI: 10.1371/journal.pone.0214098
|View full text |Cite
|
Sign up to set email alerts
|

The effect of switching costs on choice-inertia and its consequences

Abstract: In two studies we provide a novel investigation into the effects of monetary switching costs on choice-inertia (i.e., selection of the same option on consecutive choices). Study 1 employed a static decisions-from-feedback task and found that the introduction of, as well as larger, monetary switching costs led to increases in choice-inertia. While experience and decreases in the similarity of options average payouts (expected value: EV) increased choice-inertia for the option with a higher EV (the EV maximizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Thus, one natural solution to help people overcome sub-optimal inertia is to directly reduce both the perceived and the experienced costs of exploring new options. For example, Ashby and Teodorescu (2019) found that reducing the monetary costs of switching between alternatives reduced inertia biases in a binary choice setting. Similarly, reducing the costs of exploration between service providers, e.g., by enforcing transparency of prices and providing easy comparison tools, reduces information costs and tends to alleviate consumer’s inertia biases (e.g., see Timmons et al, 2019 ; Byrne et al, 2020 ; Marandola et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, one natural solution to help people overcome sub-optimal inertia is to directly reduce both the perceived and the experienced costs of exploring new options. For example, Ashby and Teodorescu (2019) found that reducing the monetary costs of switching between alternatives reduced inertia biases in a binary choice setting. Similarly, reducing the costs of exploration between service providers, e.g., by enforcing transparency of prices and providing easy comparison tools, reduces information costs and tends to alleviate consumer’s inertia biases (e.g., see Timmons et al, 2019 ; Byrne et al, 2020 ; Marandola et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…While the inaction inertia phenomenon has been replicated in multiple domains [3,4,[6][7][8][9][10][11][12][13][14][15][16][17][18] there is not a consensus on the psychological mechanism underlying the effect. Prior research suggests that inaction may be attributed to the motivation to reduce feelings of regret from missing a superior offer [3,6], or that it occurs because people devalue subsequent offers [6,11,17].…”
Section: Inaction Inertiamentioning
confidence: 99%
“…Switching costs are considered a barrier or a business strategy to maintain customer relationships (Ashby & Teodorescu, 2019). In e‐commerce, customers' usage of online systems affects their behavior of switching to other shopping channels (Chang et al, 2017).…”
Section: Research Model and Hypothesismentioning
confidence: 99%
“…Switching costs are considered a barrier or a business strategy to maintain customer relationships (Ashby & Teodorescu, 2019).…”
Section: The Influence Of E-commercementioning
confidence: 99%